Efektivitas Pemberian Susu Formula Dan Biskuit Makanan Tambahan Ibu Hamil Terhadap Ibu Hamil Kekurangan Energi Kronis (KEK) Di Puskesmas Made Kota Surabaya Tahun 2023 - Cumlaude, Shinta Besly; Siahaan, Salmon Charles (Faculty of Health Sciences , Dr. Soetomo University, 2024)
Abstract: KEK adalah keadaan kekurangan asupan energi dan protein pada wanita usia subur yang berlangsung secara terus menerus dan mengakibatkan gangguan kesehatan. Penelitian ini bertujuan untuk mengetahui efektivitas pemberian susu formula dan biskuit makanan tambahan ibu hamil terhadap ibu hamil Kekurangan Energi Kronis (KEK) di Puskesmas Made Surabaya tahun 2023. Penelitian ini dilakukan di Puskesmas Made Surabaya dan dilakukan pada bulan Januari-Desember 2023. Desain penelitian ini adalah quasi experiment dengan sampel sebanyak 13 orang ibu hamil KEK di Puskemas Made. Analisis data dilakukan menggunakan analisis univariat dan bivariat menggunakan applikasi SPSS. Analisis bivariat dilakukan menggunakan uji paired t-test (dependen t-test). Hasil analisis ditemukan rata-rata berat badan responden sebelum diberikan susu formula dan biskuit makanan tambahan ibu hamil adalah 44,35 kg dengan standar deviasi 4,578 dan rata-rata berat badan responden setelah diberikan susu formula dan biskuit makanan tambahan ibu hamil adalah 49,71 kg dengan standar deviasi 6,24. Rata-rata LILA responden sebelum diberikan susu formula dan biskuit makanan tambahan ibu hamil adalah 21,82 cm dengan standar deviasi 1,16 dan rata-rata LILA responden setelah diberikan susu formula dan biskuit makanan tambahan ibu hamil adalah 22,92 cm dengan standar deviasi 1,22. Hasil uji t-test ditemukan adaperbedaan signifikan antara berat badan responden antara sebelum dan setelah diberikan susu formula dan biskuit makanan tambahan ibu hamil (p=0,0000045) dan adaperbedaan signifikan antara LILA responden antara sebelum dan setelah diberikan susu formula dan biskuit makanan tambahan ibu hamil (p=0,000008). Kesimpulan penelitian adalah pemberian susu formula dan biskuit makanan tambahan ibu hamil efektif dalam meningkatan status gizi pada wanita KEK. Disarankan bagi puskesmas tetap mempertahankan pemberian pemberian susu formula dan biskuit makanan tambahan ibu hamil meningkatkan status gizi pada ibu hamil dengan KEK. Abstract: KEK is a condition of insufficient energy and protein intake in women of childbearing age that persists continuously and results in health problems. This study aims to determine the effectiveness of giving formula milk and additional food biscuits to pregnant women for pregnant women with Chronic Energy Deficiency (KEK) at the Made Surabaya Health Center in 2023. This research was conducted at the Made Surabaya Health Center and carried out in January-December 2023. This research design is a quasi-experiment with as many samples as possible 13 KEK pregnant women at Made Health Center. Data analysis was carried out using univariate and bivariate analysis using the SPSS application. Bivariate analysis was carried out using a paired t test (dependent t-test). The results of the analysis found that the average body weight of respondents before being given formula milk and additional food biscuits to pregnant women was 44.35 kg with a standard deviation of 4.578 and the average body weight of respondents after being given formula milk and additional food biscuits to pregnant women was 49.71 kg with a standard deviation of 6.24. The average of LILA respondents before being given formula milk and additional food biscuits for pregnant women was 21.82 cm with a standard deviation of 1.16 and the average of LILA respondents after being given formula milk and additional food biscuits for pregnant women was 22.92 cm with a standard deviation 1.22. The results of the t-test found that there was a significant difference between respondents' body weight between before and after being given formula milk and additional food biscuits for pregnant women (p=0.0000045) and there was a significant difference between respondents' LILA between before and after being given formula milk and additional food biscuits for pregnant women. pregnant (p=0.000008). The conclusion of the research is that giving formula milk and additional food biscuits to pregnant women is effective in improving the nutritional status of SEZ women. It is recommended that community health centers continue to provide formula milk and additional food biscuits for pregnant women nutritional status in pregnant women with KEK.